Design and Construction of Groundnut Oil Expeller (International Journal of Engineering and Computer Science, 2015)
Groundnut is a very important oil seed and food crop around the globe based on its nutritional and trade values, it also serves as food for humans or livestock, and in the absence of meat, forms a valuable dietary protein component. Oil extracted from groundnut by traditional means can produce about 20-30% from the groundnut whereas the mechanical methods will yield a higher percentage. A mechanical means of extracting oil was designed, constructed with locally available materials and tested for groundnut oil extraction. The machine consists of the frame, hopper, gear reduction unit and the power shaft. It was powered by a 15 hp three-phase electric motor. The expeller has an average extraction efficiency and capacity of 72.94 % and 61.4kg/hr respectively. The machine comes with a production cost of N197, 000. The expeller can be used for small scale groundnut oil extraction in the rural and urban communities